POPULATION DYNAMICS OF WHITE CRESTED KALIJ PHEASANT LOPHURA LEUCOMELANOS HAMILTONI (GRAY), IN GARHWAL HIMALAYA - KUMAR, SUNEET; BISHT, M.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Present paper reports some observation on population dynamics of White crested kalij pheasant Lophura leucomelanos hamiltoni in Garhwal Himalaya, Uttarakhand India during November 2007 to April 2009. In 405 sightings, 1772 Kalij were recorded with overall 2.74 density (birds/km). 5.62 group size and 1.34:1.0 sex-ratio between male and female. Significant seasonal variation was also recorded in density and group size. Maximum values of density 10.93+3.46 birds/km in the winter and average group size (7.58+2.08) in the monsoon and post monsoon season were noticed whereas minimum for the same recorded in the summer season. Incidences of hunting were recorded in all the seasons except summer.